2012
DOI: 10.1682/jrrd.2011.05.0095
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of Internet-based early intervention for combat-related mental distress

Abstract: Abstract-This article evaluates an Internet-based early intervention combining online cognitive-behavioral therapy (CBT) with electronic peer-to-peer support intended to promote mental health and well-being among combat veterans. We conducted a phase 1 clinical trial of 50 Iraq and Afghanistan veterans using a pre and post single-arm design. We evaluated feasibility and changes in mental health symptoms (depression and posttraumatic stress disorder [PTSD]), functional status, and attitudes toward treatment see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…However, evidence from our study suggests that unit support may be a resiliency factor for anger. Other work has demonstrated that greater perceived support and connection with peers is a potential protective factor against depression (Brenner, Homaifar, Adler, Wolfman, & Kemp, 2009; Pietrzak et al, 2010; Van Voorhees, Gollan, & Fogel, 2012) and ameliorates difficulties encountered during transitions between military and civilian life (Ahern et al, 2015). We also know from previous work that veterans report feeling more comfortable speaking about their experiences with other veterans who understand them (Hinojosa & Hinojosa, 2011; Laffaye et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence from our study suggests that unit support may be a resiliency factor for anger. Other work has demonstrated that greater perceived support and connection with peers is a potential protective factor against depression (Brenner, Homaifar, Adler, Wolfman, & Kemp, 2009; Pietrzak et al, 2010; Van Voorhees, Gollan, & Fogel, 2012) and ameliorates difficulties encountered during transitions between military and civilian life (Ahern et al, 2015). We also know from previous work that veterans report feeling more comfortable speaking about their experiences with other veterans who understand them (Hinojosa & Hinojosa, 2011; Laffaye et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The innovative use of technology such as computers/tablets/smartphones may help increase adoption through facilitating virtual social and professional support while avoiding transportation barriers. 55 Others have successfully used peer-support 56, 57 within internet-based interventions promoting behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the intervention can serve a variety of purposes, such as real-time symptom monitoring and homework assignment [23]. For example, an Internet-based intervention for combat-related mental distress that included facilitated peer support was found to decrease depression symptoms and social stigma related to mental health issues among combat Veterans [24]. Mental health providers' direct clinical involvement in self-guided Internet interventions varies greatly, and most current interventions are used as adjunct to or in lieu of traditional psychotherapy.…”
Section: Internet-based Interventionsmentioning
confidence: 99%
“…The first aim was to address the current gaps in research by identifying willingness to use a variety of emental health modalities as a means for accessing mental health services in diverse Veterans with and without a positive screen for PTSD. Based on previous studies that indicate that Veterans with PTSD are interested in using e-health modalities [22,24,40] and drawing from Andersen's Behavioral Model [47], we hypothesized that Veterans with PTSD would report greater willingness to use emental health than Veterans without PTSD. Additionally, research has not examined interest in e-health modalities in Veterans who express a need for traditional mental health services.…”
Section: Study Aims and Hypothesesmentioning
confidence: 99%